PRAGMALINGUISTIC FEATURES OF TEXT AND LANGUAGE ADVERTISING (World Bulletin of Social Sciences, 2022)
This article emphasizes the scientific basis, text and language of advertising. Formation of speech of advertising depends on cultural feature and distinguishing literary texts. The aim of this work is to provide an up-to-date account for the language used in advertising from linguistic and stylistic points of view.